Gender differences in the impact of the COVID-19 pandemic on psychological well-being: evidence from Japan - Raymo, James M.; Uchikoshi, Fumiya; Yuri, Shiina (Asian Population Studies, 2024)
We advance research on the 'gendered pandemic' and its implications for psychological well-being in three important ways. First, we focus on Japan, arguably the most gender-inegalitarian wealthy country. Second, we focus on gender differences in both hedonic and eudaimonic well-being. Third, we use demographic decomposition tools to evaluate the extent to which observed gender differences in decline in psychological well-being reflect differences in pre-pandemic characteristics, differences in life changes during the pandemic, differences in pandemic-related worry, and differences in men's and women's responses to these characteristics and experiences. Results show that decline in both dimensions of psychological well-being was significantly greater for women and that the contributions of differences in relationships were larger than those of differences in composition. We also show that reduction in well-being derived from social interaction was particularly pronounced for women and that gender differences in age patterns of decline in both dimensions of psychological well-being are large.
Keywords: COVID-19 Pandemic; Gender Difference; Japan; Psychological Well-Being; Decomposition